Market reaction to the company's name change: empirical evidence from Malaysia - Ahmad Azham, Zakaria (2019)
This study aims to examine the market reaction to the announcement of company's name changes. The sample of this this study consists of the announcements of the company's name changes made by Malaysian companies during the period of year 2014 to 2018. This study uses an event study methodology to examine the effects of the announcement to the stock price of the company. The effect of signaling theory and information asymmetry hypothesis has been observed to explain the relation of the company's name change announcement. Using an event study methodology, the results of this study show that there is no significant effect on abnormal returns to the changes of company's name announcements. Despite the negative figure on the announcement date but there is no significant impact on the stock price. In addition, this study also found that there is no significant impact on the abnormal returns prior and post of the announcement date. Overall, it can be concluded that signaling information and information asymmetry hypothesis done by the companies to the investors through company's name change announcement does not significantly affect the shareholder's wealth.